Operations Research Proceedings 2012 : Selected Papers of the International Annual Conference of the German Operations Research Society (GOR), Leibniz University of Hannover, Germany, September 5-7, 2012 - Helber, Stefan; Breitner, Michael; Rosch, Daniel; Schön, Cornelia; Graf von der Schulenburg, Johann-Matthias; Sibbertsen, Philipp; Steinbach, Marc; Weber, Stefan; Wolter, Anja (Operations Research Proceedings, GOR (Gesellschaft für Operations Research e.V.),, 2014)
This book contains selected papers presented at the "International Annual Conference of the German Operations Research Society (OR2012)" which was held September 4 -7, 2012 at the Leibniz Universität Hannover, Germany. The international conference, which also serves as the annual meeting of the German Operations Research Society (GOR), attracted more than 500 participants from more than 39 countries. Special attention at the conference was given to the three topics "Energy, Markets and Mobility". The OR2012 conference has addressed these topics from an OR perspective, treating them not only in isolation, but also with respect to their numerous and exciting interconnections, such as new energy for new mobility concepts and new market mechanisms for sustainable energy production to name but a few. The proceedings show that this conference topic is an important and promising area to apply Operations Research. The book also contains numerous papers addressing the full scope of fields in Operations Research.